THE PARADIGM SHIFT FROM PRINT TO DIGITAL MEDIA: AN EVALUATIVE STUDY - Rai, Vinay Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The relevance of media is increasing daily as it connects the globe and enables us to evaluate every piece of information, we get daily. At present, media may be classified into three segments- Print Media, Electronic Media and Digital Media. These all have their own opinions, importance and uniqueness. Media consumption is undergoing a significant shift in consumption patterns. Digital media with the help of technologies and the digital transformation now plays a significant role in every industry, including business, education, politics, medicine, marketing, and communication. The transition of the news media to digital has caused significant change in the industry, including several of new providers. This paper focuses on impact of digital media on print media and how it created a physical and digital space. The following aims to provide information regarding the digital transformation by conducting a systematic literature review.